Resistance to aztreonam-avibactam due to a mutation of SHV-12 in Enterobacter - Shikai Wu; Ke Ma; Yu Feng; Zhiyong Zong (BMC, 2023)
Abstract Aztreonam-avibactam is an important option against Enterobacterales producing metallo-β-lactamases (MBLs). We obtained an aztreonam-avibactam-resistant mutant of an MBL-producing Enterobacter mori strain by induced mutagenesis. Genome sequencing revealed an Arg244Gly (Ambler position) substitution of SHV-12 β-lactamase in the mutant. Cloning and susceptibility testing verified that the SHV-12 Arg244Gly substitution led to significantly reduced susceptibility to aztreonam-avibactam (MIC, from 0.5/4 to 4/4 mg/L) but with the loss of resistance to cephalosporins as tradeoff. Arg244 of SHV involves in the binding of avibactam by forming an arginine-mediated salt bridge and is a critical residue to interact with β-lactams. Molecular modeling analysis demonstrated that the Arg244Gly substitution hindered the binding of avibactam to SHV with higher binding energy (from − 5.24 to -4.32 kcal/mol) and elevated inhibition constant Ki (from 143.96 to 677.37 µM) to indicate lower affinity. This substitution, however, resulted in loss of resistance to cephalosporins as tradeoff by impairing substrate binding. This represents a new aztreonam-avibactam resistance mechanism.